Investigation of sphingosine kinase 1 in interferon responses during dengue virus infection. Issue 7 (21st July 2017) - Aloia, Amanda L; Calvert, Julie K; Clarke, Jennifer N; Davies, Lorena T; Helbig, Karla J; Pitson, Stuart M; Carr, Jillian M
Abstract : Dengue virus (DENV) regulates sphingosine kinase (SK)‐1 activity and chemical inhibition of SK1 reduces DENV infection. In primary murine embryonic fibroblasts (pMEFs) lacking SK1 however, DENV infection is enhanced and this is associated with induction of normal levels of interferon beta (IFN‐β) but reduced levels of IFN‐stimulated genes (ISGs). We have further investigated this link between SK1 and type I IFN responses. DENV infection downregulates cell‐surface IFN‐alpha receptor (IFNAR)1 in both wild‐type (WT) and SK1 − /− pMEF, but, consistent with poor ISG responses, shows reduced induction of phosphorylated (p)‐STAT1 and key IFN regulatory factors (IRF)1 and −7 in SK1 −/− pMEF. Direct IFN stimulation induced ISGs (viperin, IFIT1), CXCL10, IRF1 and −7 and p‐STAT1. Responses, however, were significantly reduced in SK1 −/− pMEF, except for IFN‐stimulated CXCL10 and IRF7. Poor IFN responses in SK1 −/− pMEF were associated with a small reduction in basal cell‐surface IFNAR1 and IRF1 mRNA in uninfected SK1 −/− compared with WT pMEF. In contrast, treatment of cells with the SK1 inhibitor, SK1‐I or expression of an inhibitory SK1 short hairpin RNA (shRNA), both of which reduce DENV infection, does not alter basal IRF1 mRNA or affect type I IFN stimulation of p‐STAT1. Thus, cells genetically lacking SK1 can induce many responses normally following DENV infection, but have adaptive changes in IFNAR1 and IRF1 that compromise DENV‐induced type I IFN responses. This suggests a biological link between SK1 and IFN‐stimulated pathways. Other approaches to reduce SK1 activity, however, do not influence these important antiviral pathways but reduce infection and may be useful antiviral strategies. Dengue virus: Enzyme associated with susceptibility to infection: An enzyme linked to susceptibility to dengue virus can affect how cells mount an interferon‐mediated anti‐viral immune response. Sphingosine kinase 1 (SK1) normally controls whether cells proliferate or survive. It was known that the dengue virus could alter the enzyme/s function, but it was not clear why chemically blocking SK1 reduced dengue infectivity whereas cells that genetically lacked a working copy of SK1 were more susceptible to dengue infections. An Australian research team led by Jillian Carr from Flinders University in Adelaide showed that cells genetically missing SK1, but not those treated with an inhibitor of the enzyme, had reduced levels of type I interferon, a driver of anti‐viral immunity. The findings highlight the complexity of manipulating SK1 in different cell systems, —an insight that could help guide further drug development against this potential therapeutic target.